THE INFLUENCE OF AN INCLUSIVE FUNDRAISING STRATEGY BASED ON RELIGIOUS MODERATION ON THE DONATION INTEREST OF THE BOGOR REGENCY COMMUNITY - Roisiyatin; Wildan Munawar; Egi Agustian Rahmat Sukendar (Academic Bright Collaboration, 2026)
This study investigates the influence of an Inclusive Fundraising Strategy (IFS) grounded in religious moderation on Public Donation Interest (PDI) in Bogor Regency, Indonesia. It addresses the persistent gap between the region’s substantial philanthropic potential and its relatively low realization by examining whether inclusive fundraising practices can enhance public willingness to donate across religious communities. A quantitative explanatory survey design was employed using purposive sampling. Data were collected from 100 respondents representing diverse religious backgrounds in Bogor Regency through a structured five-point Likert-scale questionnaire. The data were analyzed using SPSS, including validity and reliability tests, classical assumption tests, simple linear regression, t-test, and coefficient of determination (R²). The results reveal that IFS has a positive and statistically significant effect on PDI (β = 0.484; p < 0.001). The regression model indicates that improvements in inclusive fundraising practices are associated with higher public donation interest. However, the model explains 23.4% of the variance in donation interest, suggesting that other determinants also influence individuals’ willingness to donate. The findings encourage philanthropic organizations to strengthen inclusivity, transparency, accessibility, and religious moderation within their fundraising strategies. Nevertheless, the cross-sectional design, single-predictor model, limited sample size, and focus on Bogor Regency restrict the generalizability of the findings. Future studies should incorporate additional variables and broader geographical coverage. This study offers an empirical contribution by integrating religious moderation into the concept of inclusive fundraising strategy and quantitatively demonstrating its association with public donation interest.